Surgical intervention for Kasaback-Merritt Syndrome: A case report - Morris Sasson; J. Alford Flippin; Gary Birken; Fuad Alkhoury (Elsevier, 2015)
Kasabach-Merritt Syndrome (KMS) is an uncommon phenomenon characterized by the presence of a vascular tumor in association with thrombocytopenia, consumption coagulopathy and hemodynamic instability. Typically presents in infancy and involve the skin and deep soft tissues of the arms and legs. Treatment options vary with clinical presentation, and ranges from medical management to immediate surgical intervention. We present an unusual case of a newborn with KMS and fatal hemodynamic collapse imminent, which was successfully treated with surgical resection at our institution.